The Impact of Building Design on Energy Savings Case Study: Main Building of the Ministry of Public Works and Housing (PUPR) – Jakarta - Arif Rahmadi , Arfat; Hastijanti , RA Retno; Tjahja Prakasa , Darmansjah (International Conference of Innovation and Community Engagement, 2024)
The Main Building Design of the Public Works and Public Housing Ministry (PUPR) in Jakarta has a significant impact on energy savings inside, according to the Jatmika Adi Suryabrata (Department of Architecture and Planning, UGM), in 1 month this building achieved Energy Cost Savings of more than IDR 230 million. This paper analyzes building design elements that contribute to increasing energy efficiency, examines four key design elements: building mass form, façade materials, natural lighting, and shading. Each of these elements plays a crucial role in enhancing energy efficiency in the main building of the Ministry of Public Works and Housing.. In addition, the aspect of resilience is a crucial element of the design, ensuring that the building can withstand climate change and potential disasters. Through a case study approach and empirical data analysis, the research results show that efficient building design can reduce electricity consumption by up to 30-50%. These findings confirm that appropriate building design can be a key factor in achieving energy efficiency as well as offering significant economic, environmental, and resilience benefits for government buildings.